Chitosan from Gonggong Snail Shells to Reduce Iron (Fe) Levels in Dug Well Water in Andana Residence Housing, Batu IX Village, Riau Islands - Hevi Horiza; Iwan Iskandar; Mutia Yuhesti (Aloha International Journal of Health Advancement (AIJHA), 2025)
Dug well water often contains organic and inorganic components, including various dangerous metals that are commonly found in it, such as iron (Fe). Therefore, this research aimed to determine the combination of aeration and filtration methods using chitosan from gonggong shells to reduce Fe levels in dug well water in the Andana Housing Complex, Tanjungpinang City. This research implemented a pre-experimental design. Water samples were obtained from 10 dug wells in the Andana Housing Complex, Tanjungpinang City. The samples were treated with a combination of aeration and filtration methods using chitosan from gonggong shells. Before and after treatment, physical conditions of the water were observed and laboratory tests were carried out to measure Fe levels. After treatment, it was discovered that the smell, color and taste disappeared. Meanwhile, there was also a decrease in Fe levels of 80.95% for gonggong snail shell chitosan with a thickness of 1 cm, 84.93% for a thickness of 3 cm, and 98.33% for a thickness of 5 cm. It was concluded that the combination of aeration and filtration methods using chitosan from gonggong shells was effective in improving the physical conditions of water and reducing Fe levels in water. Suggestions for further research include: improving this research by adding other media to reduce Fe levels or combining it with filtering media and other methods. Suggestions for the community to process chitosan from gonggong snail shells in water treatment containing Fe and offer the government to socialize the use of chitosan filtration from gonggong snail shells. Keywords: dug well; Fe; gonggong snail shell; chitosan